IMPLEMENTASI PENDEKATAN KOOPERATIF DAN KOLABORATIF MENGGUNAKAN MEDIA PASAR MATEMATIKA PADA SISWA KELAS 1 UPT SD NEGERI SURUHWADANG 01 - Nurfahmi Khoirunisa, Dinadya; Surayanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student engagement and difficulties in understanding numerical concepts remain primary challenges in mathematics education. Many first-grade students at UPT SD Negeri Suruhwadang 01 experience anxiety or difficulty when learning methematics due to conventional and monotonous teaching methods. This study aims to examine how the implementation of cooperative and collaborative approaches through the Mathematics Market media can transform the learning environment. This research employs a descriptive qualitative method in the form of a case study, focusing on the implementation of cooperative and collaborative using Mathematics Market media. Data were collected through direct observation of student activities, interviews, and documentation of classroom sessions. The result indicate that role-playing within the Mathematics Market significantly increases student communication and peer cooperation. Furthermore, mathematical consepts that were previously perceived as difficult became easier to grasp as student practiced them through hand-on experience. In conclusion, group learning methods supported by game-based media are highly effective in enhancing the enthusiasm and methematical comprehension of first-grade elementary school students.